2017
DOI: 10.21460/jrmb.2016.111.257
|View full text |Cite
|
Sign up to set email alerts
|

Devidend Pay Out Ratio Pada Emiten Manufaktur Di Bursa Efek Indonesia

Abstract: This study aims to analyze and empirically test the significance of partial and simultaneous effect ofinsider ownership, DER, ROE, firm size, IOS, PER, and EPS Dividend Payout Ratio (DPR) inmanufacturing companies in Indonesia Stock Exchange of 2008 - 2013 period. The results showedthat partially turned out just ROE, IOS, PER, and EPS significantly influence of dividend payoutratio, while the insider ownership, DER, and firm size does not affect significant. Meanwhilesimultaneously, all variables INSDOWN, DER,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This empirical evidence is in line with investigations conducted by Benu et al, (2023); A. Handayani & Santoso, (2021);and Wijaya & Solikhin, (2018) who confirmed that return on assets positively and significantly influences the dividend payout ratio.…”
Section: Relationship Between Return On Assets and Dividend Payout Ratiosupporting
confidence: 92%
See 1 more Smart Citation
“…This empirical evidence is in line with investigations conducted by Benu et al, (2023); A. Handayani & Santoso, (2021);and Wijaya & Solikhin, (2018) who confirmed that return on assets positively and significantly influences the dividend payout ratio.…”
Section: Relationship Between Return On Assets and Dividend Payout Ratiosupporting
confidence: 92%
“…Another study was also found in Mutiarahim's literature, (2020), namely, that return on investment and debt to equity ratio do not influence the dividend payout ratio. Further research from Benu et al, (2023);and Handayani & Santoso, (2021) The debt-to-equity ratio does not affect the dividend payout ratio, while the return on assets significantly affects it. The empirical analysis also found a different conclusion.…”
Section: Introductionmentioning
confidence: 95%
“…Investors who have high expectation, businesses will need to perform better in order to grow profits. As a result, each business will be able to pay shareholders a higher dividend (Kowanda et al, 2017).…”
Section: The Effect Of Price Earning Ratio On Dividend Policy Ratiomentioning
confidence: 99%
“…The amount that investors anticipate a company will grow is reflected in its stock price. Investors' high expectations for earnings growth are reflected in high stock prices for companies, and vice versa (Kowanda et al, 2017). A company's dividend policy will rise in response to an increase in the PER.…”
Section: The Introductionmentioning
confidence: 99%